Mononeuritis multiplex in a patient with B-cell prolymphocytic leukaemia: a diagnostic challenge. (2nd September 2013) - Le Clech, Lenaïg; Rizcallah, Marie Jeanne; Alavi, Zarrin; Hutin, Pascal
Abstract : B-cell prolymphocytic leukaemia (BPLL) is a haematological malignancy defined as lymphocytosis and splenomegaly with >55% circulating cells being clonal prolymphocytes of B-cell origin. The evolution of this disease is more aggressive than chronic lymphocytic leukaemia. We reported a case of a 62-year-old man with BPLL who, on treatment, attained cytological, immunophenotypic and complete cytogenetic remission. He subsequently developed an asymmetric sensorimotor neurological disorder, suggestive of lymphomatous infiltration (neurolymphocytosis). Repetition of the MRI and the electromyography was essential for diagnosis. Progressive mononeuritis multiplex in B-cell leukaemias/lymphomas is rare and may be the only presenting symptom of relapsed or progressive disease. Repeat imaging studies based on judicious evaluation of the clinical scenario for exclusion of other causes of neurological symptoms is necessary. This can be challenging in patients with long-standing malignancies who have received multiple courses of chemotherapy and/or radiotherapy.